A múltipla pertença religiosa do indígena : a evangelização das Assembleias de Deus no povo Xukuru do Ororubá de 1980 a 2022 - Silva, Yuri Magalhães (2023)
The present study is a field and qualitative action research that investigates the hybridity in the evangelization of the Assemblies of God (ADs) in the indigenous people Xukuru do Ororubá from 1980 to 2022 in the municipality of Pesqueira, rural Pernambuco, comprising the multiple indigenous and religious affiliations the format of assembly evangelization that is deconstructed and reconstructed without losing something or practice that refers to the indigenous way of being. With the breakup of the State and the (Catholic) Church at the beginning of the Brazilian Republic, a fertile field for new religions was created in a Brazil that was deep and full of contrasts, but it was not until the 1980s that the ADs became a Pentecostal corporation and expand close to the Xukuru indigenous territory. In the gaps left, many counterattacks are undertaken and a range of arrows shot that we don't know where they will fall and who they will hit, are the attempts and possibilities of invention of a Christian world. On the other hand, politicizing the village and village politics are movements that impact the evangelization of a village people. Furthermore, the indigenous camouflage themselves to fit into another religious community, however, even denying their ancestors, they maintain their roots in a multiple religious belonging. Max Weber's typologies of power and domination, Pierre Bourdieu's concept of the symbolic field, Stuart Hall's identity crisis at a crossroads of uncertain interactions of order/disorder, subject/object of Edgar Morin's complexity theory offer a theoretical weight for the proposed analysis.